Estimation Efficiency Hospitals of Kerman Province Using Stochastic Frontier Analysis (SFA) Method, 2007-2011 - Reza Goudarzi; Elham Haghighat fard; Leila Vali; MohammadReza Baneshi; Payam Haghighat fard; Banafsheh Darvishi (Kerman University of Medical Sciences, 2015)
Introduction: One of the most fundamental goals of most countries is improving the quality and efficiency level of healthcare systems and efficient use of their resources. In this regard, the efficient use of facilities and equipments for the hospitals, that are considered as one of the most costly health care delivery organizations, is particularly important. The goal of this survey was the efficiency estimation of hospitals in Kerman Province (2007-2011). Method: In this econometric study, performance of 10 hospitals in Kerman Province was analyzed in 5 years, using panel data for Stochastic Frontier Analysis (SFA) method. Production factors such as number of beds, doctors, nurses, and out patient admissions were used as inputs, and numbers of outpatient admissions have been selected as outputs. Frontier version 4.1 was used to analyze data. Results: Based on SFA method, the average performance of hospitals was 0.648, so we concluded that the capacity of improving performance in these hospitals can be increased to 0.352 percentages. Conclusion: Based on findings of this study, adjusting surplus manpower, congenital planning for increasing efficiency and resourcing management should be the priority of objectives of the managers and directors so that we can increase the level of efficiency of hospitals and reduces costs to the minimum as possible. Keywords: Education Hospitals, Efficiency, Stochastic Frontier Analysis (SFA) Citation: Goudarzi R, Haghighat fard E, Vali L, Baneshi MR, Haghighat fard P, Darvishi B. Estimation Efficiency Hospitals of Kerman Province Using Stochastic Frontier Analysis (SFA) Method, 2007-2011. Journal of Health Based Research 2015 1(2):105-114.